Marketing strategy of the new product introduction on the market - Zdenka Kádeková; Lubica Kubicova (Polityki Europejskie, Finanse i Marketing)
The paper points at the choosing the effective marketing strategy when introducing the new product on the market. In today´s market the supply of the most products prevails over their demand. If the market is saturated, the innovation is one of the important tools for the intensive products penetrating to the customers. The aim of the product innovation is the partial change, improvement of the current performance as well as the substantial changes and creation of the entirely new products. The important sources of innovation include basic and applied research, which can afford mostly the strong and large companies such as Danone Group that is the largest producer of fresh dairy products in the world and the world´s second largest supplier of the mineral water.